Implementasi Teknologi Barcode Untuk Pintu Ruangan Dengan PI Camera - Nayandra Fahri Himawan; Rizki Aditiya Ramadan; Tri Melda Yama (Journal of Digital Literacy and Volunteering, 2023)
Providing a door security system makes it essential that the latest technology is being applied to carry out this purpose. University classrooms usually implement automatic door locks equipped with sensors to allow access to the classroom. Door access requires more autonomous, integrated and intelligent functions to enhance the usability of automatic smart locks. This research demonstrates the development of a secure door lock system using Quick Response (QR) technology and PI Camera to access classrooms at universities where authorized persons will also be able to monitor who has accessed the classroom. The system can log data and track entry and exit access when accessing the security door from the website server. In this case, the authorized individual will only get permission to access the door. This is initial work to test the function of the system for property and facility use such as in offices, universities, and laboratories. Based on the results and data collection, the testbed development has worked well as a preliminary study to provide smart security doors using QR Code.